Analisis Pelaksanaan Lelang Sebagai Tindak Lanjut Eksekusi Hak Tanggungan Perspektif Undang-Undang Nomor 4 Tahun 1996 Tentang Hak Tanggungan Atas Tanah Beserta Benda-Benda Yang Berkaitan Dengan Tanah - Ramadita, Ivan Yosa Ari; Yunanto, Yunanto (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Law Number 4 of 1996 is the mandate of the Basic Agrarian Law, namely the unification of security institutions in Indonesia. The purpose of this study is to analyze the juridical implementation of the execution of mortgage rights based on the perspective of Law Number 4 of 1996 concerning mortgage rights on land and objects related to land (study of the execution of mortgage rights in the jurisdiction of KPKNL Banjarmasin). The method in this research uses empirical normative legal research. The results of this study: 1) Overview of Mortgage Rights in accordance with Law No. 4 of 1996 is to guarantee the debt of the taggungan holder to the debtor and the ownership of the certificate is suspended, if the dependents have been repaid then the certificate can be abolished as collateral. 2)The execution of mortgage rights in accordance with Law No. 4 of 1996 on mortgage rights carried out by KPKNL Banjarmasin is carried out with court intervention and without court intervention to provide a decision or determination of execution.